Quality of correspondence administration services using electronic signatures at the regional secretariat of gianyar regency - Karyawati, Ni Putu; Rulinawaty, Rulinawaty; Sugiono, Arif (Jurnal Mantik, 2024)
Administrative correspondence services at the Gianyar District Secretariat play a vital role in supporting the efficiency and effectiveness of public services. The use of electronic signatures is an innovation aimed at enhancing the quality of these services. However, further research is needed to evaluate the extent to which the implementation of electronic signatures has had a positive impact. This study aims to describe the quality of administrative correspondence services using electronic signatures at the Gianyar District Secretariat and to evaluate its influence on service efficiency and effectiveness. This research employs a qualitative approach with a case study design. Primary data were obtained through interviews and observations with officials and staff at the District Secretariat. Secondary data were collected from documentation of relevant regulations. The results indicate that the implementation of electronic signatures has improved the efficiency of administrative correspondence processes at the Gianyar District Secretariat. 85% of respondents expressed satisfaction with the services provided. Therefore, the use of electronic signatures can enhance the quality of administrative correspondence services at the Gianyar District Secretariat. Recommendations to further optimize the use of technology in public services are also suggested